The Importance of Digital Media Literacy in Family - Wandi Wandi (State Islamic Institute of Bone, Indonesia, 2022)
Digital media is a necessity that always accompanies family activities, this has also become a new habit in family environment in the new normal era and also to adapt to the technological developments and developing communication situations. This phenomenon reinforces that media literacy in family is something that is crucial to be an attention for parents in protecting the family from the consequences that can be caused by the use of digital media which can damage the children’s life and adolescents in family. Hence, the role of parents is needed, such as: (1) Parents have to monitor children's activities so they feel their parents' attention. (2) Parents can play with children while directing children to open content that is useful for their learning development. (3) Parents can provide time limits for children in using digital media to avoid the dangers of addiction. So the negative impacts that can damage the psychology and behavior of children in family such as content that leads to violence, pornography, and cyberbullying as well as foreign cultural influences can be avoided and the positive impacts of digital media can be used well by children.